Preparation method of high-toughness wood-plastic composite wire for 3D printing

By using EMA-GMA as a toughening agent and compatible agent in wood-plastic composite materials, and using multiple melt extrusion and wire drawing processes, the problem of poor compatibility between wood fibers and thermoplastics is solved, and the toughness of the material is significantly improved and compatibility, meets the needs of 3D printing.

CN119408158AActive Publication Date: 2025-02-11NORTHEAST FORESTRY UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411663252.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-11
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing wood fibers have poor compatibility with thermoplastics, resulting in rough surfaces and low toughness of wood-plastic composite wires, which affect mechanical properties and printing stability.

Method used

Ethylene-methyl acrylate-glycidyl methacrylate copolymer (EMA-GMA) is used as toughening agent and compatible agent, and the compatibility of wood fibers and polylactic acid is improved through primary and secondary melt extrusion and wire drawing processes. Sex and resilience.

Benefits of technology

It significantly improves the toughness and compatibility of wood-plastic composite wires, improves the mechanical properties and printing stability of the material, meets the needs of 3D printing, and conforms to the concept of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119408158A_ABST
    Figure CN119408158A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-toughness wood-plastic composite wire rod for 3D printing, and belongs to the field of wood-plastic composite materials. The invention aims to solve the problems of rough surface and low toughness of the wood-plastic composite wire rod caused by poor compatibility of the existing wood fiber and thermoplastic plastic. The method comprises the following steps: 1, weighing; 2, primary melt extrusion; 3, carrying out secondary melt extrusion; and 4, wire drawing. The preparation method is used for preparing the high-toughness wood-plastic composite wire for 3D printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wood-plastic composite materials. Background Art

[0002] At present, the research on wood-plastic consumables for 3D printing in China mainly focuses on the preparation of composite filaments, using wood fibers and polymers, adding different additives and performing 3D printing by melt deposition method.

[0003] However, after the addition of wood fiber, the surface of the wood-plastic composite wire is relatively rough and the toughness is low due to the poor compatibility of wood fiber with thermoplastics, which in turn affects the mechanical properties of the material and reduces the printing stability, such as uneven discharge and wire breakage. For wood-plastic composite wires, improving the toughness of the wire can significantly improve the smoothness of the printing process, the structural integrity, impact resistance, model accuracy and surface quality of the product. Summary of the invention

[0004] The present invention aims to solve the problem that the existing wood fiber and thermoplastic plastic have poor compatibility, resulting in a rough surface and low toughness of the wood-plastic composite wire, and further provide a method for preparing a high-toughness wood-plastic composite wire for 3D printing.

[0005] A method for preparing a high-toughness wood-plastic composite wire for 3D printing is carried out according to the following steps:

[0006] 1. Weighing:

[0007] Weigh 1 to 30 parts of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 35 to 65 parts of polylactic acid, 10 to 40 parts of wood fiber and 1 to 3 parts of fluidity modifier according to mass proportions;

[0008] 2. One-step melt extrusion:

[0009] The weighed ethylene-methyl acrylate-glycidyl methacrylate copolymer and polylactic acid are mixed evenly, and then melt-extruded once using a single-screw extruder, and finally cooled, crushed and granulated to obtain a blended polymer;

[0010] 3. Secondary melt extrusion:

[0011] The weighed wood fiber, the fluidity modifier and the blended polymer prepared in step 2 are mixed evenly, and then a twin-screw extruder is used for secondary melt extrusion, cooling, crushing and granulation, and finally drying to obtain wood-plastic granules;

[0012] 4. Wire drawing:

[0013] The wood-plastic pellets are drawn using a single-screw wire drawing machine, and then water-cooled and reeled to obtain high-toughness wood-plastic composite wires for 3D printing.

[0014] The beneficial effects of the present invention are:

[0015] 1. The present invention uses wood powder with a higher mesh count to improve the dispersion of the wood powder in the plastic matrix. On the other hand, ethylene-methyl acrylate-glycidyl methacrylate copolymer (EMA-GMA) is selected as a toughening agent between wood fiber and polylactic acid to effectively improve the toughness of the material.

[0016] 2. The present invention improves the compatibility and melt flow problems between wood and plastic by means of secondary granulation, balances the cost-effectiveness and toughness of the wire, and achieves the purpose of improving the printability of wood-plastic composite wire. During the first granulation, the melting temperature of PLA and EMA-GMA is set at 120°C to 230°C, in order to make the epoxy groups in glycidyl methacrylate react with the hydroxyl and carboxyl groups in the PLA molecular chain to form crosslinks. In the secondary granulation, EMA-GMA acts as a toughening agent and compatibilizer, which can transfer and disperse stress when the material is subjected to external force, reduce the generation and expansion of cracks, and improve the overall toughness of the material.

[0017] 3. The wire material produced by the present invention has the natural affinity of wood, stable size, smooth surface, and low processing conditions. The printed products do not warp or clog, have certain toughness, and meet the needs of 3D printing. The printed products have good physical and mechanical properties and strong weather resistance, and conform to the concept of green environmental protection. The materials or products can save costs to a certain extent.

[0018] The method for preparing a high-toughness wood-plastic composite wire for 3D printing provided by the present invention has the advantages of simple preparation, low cost, good toughness, etc., and provides a new idea for expanding the application scenarios of the wood-plastic composite wire.

[0019] Attached Notes

[0020] Figure 1 This is a physical picture of the high-toughness wood-plastic composite wire prepared in Example 1;

[0021] Figure 2 This is a real picture of the sample after 3D printing using high-toughness wood-plastic composite wire in Example 4. DETAILED DESCRIPTION

[0022] Specific implementation method 1: This implementation method is a method for preparing a high-toughness wood-plastic composite wire for 3D printing, which is carried out according to the following steps:

[0023] 1. Weighing:

[0024] Weigh 1 to 30 parts of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 35 to 65 parts of polylactic acid, 10 to 40 parts of wood fiber and 1 to 3 parts of fluidity modifier according to mass proportions;

[0025] 2. One-step melt extrusion:

[0026] The weighed ethylene-methyl acrylate-glycidyl methacrylate copolymer and polylactic acid are mixed evenly, and then melt-extruded once using a single-screw extruder, and finally cooled, crushed and granulated to obtain a blended polymer;

[0027] 3. Secondary melt extrusion:

[0028] The weighed wood fiber, the fluidity modifier and the blended polymer prepared in step 2 are mixed evenly, and then a twin-screw extruder is used for secondary melt extrusion, cooling, crushing and granulation, and finally drying to obtain wood-plastic granules;

[0029] 4. Wire drawing:

[0030] The wood-plastic pellets are drawn using a single-screw wire drawing machine, and then water-cooled and reeled to obtain high-toughness wood-plastic composite wires for 3D printing.

[0031] The beneficial effects of this embodiment are:

[0032] 1. This embodiment uses wood powder with a higher mesh count to improve the dispersion of the wood powder in the plastic matrix. On the other hand, ethylene-methyl acrylate-glycidyl methacrylate copolymer (EMA-GMA) is selected as a toughening agent between wood fiber and polylactic acid to effectively improve the toughness of the material.

[0033] 2. This embodiment uses a secondary granulation method to improve the compatibility and melt flow problems between wood and plastic, balance the cost-effectiveness and toughness of the wire, and achieve the purpose of improving the printability of wood-plastic composite wire. During the first granulation, the melting temperature of PLA and EMA-GMA is set at 120°C to 230°C, in order to react the epoxy groups in glycidyl methacrylate with the hydroxyl and carboxyl groups in the PLA molecular chain to form crosslinks. In the secondary granulation, EMA-GMA acts as a toughening agent and compatibilizer, which can transfer and disperse stress when the material is subjected to external forces, reduce the generation and expansion of cracks, and improve the overall toughness of the material.

[0034] 3. The wire material produced in this embodiment has the natural affinity of wood, stable size, smooth surface, and low processing conditions. The printed product does not warp or clog, has a certain toughness, and meets the needs of 3D printing. The printed product has good physical and mechanical properties and strong weather resistance, and conforms to the concept of green environmental protection. The material or product can save costs to a certain extent.

[0035] The method for preparing a high-toughness wood-plastic composite wire for 3D printing provided in this embodiment has the advantages of simple preparation, low cost, good toughness, etc., and provides a new idea for expanding the application scenarios of wood-plastic composite wires.

[0036] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the mass percentage of glycidyl methacrylate monomer in the ethylene-methyl acrylate-glycidyl methacrylate copolymer described in step 1 is 1% to 8%. Other aspects are the same as specific embodiment 1.

[0037] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the melt mass flow rate of the polylactic acid described in step 1 is 3 g / 10 min to 10 g / 10 min under the conditions of a temperature of 210° C. and a load of 2.16 kg. The rest is the same as specific embodiment 1 or 2.

[0038] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: the wood fiber described in step 1 is one or a mixture of wood powder, rice husk powder, bamboo powder, straw powder, fruit shell powder and bagasse; the mesh number of the wood fiber described in step 1 is 60 mesh to 200 mesh. The rest is the same as specific embodiments 1 to 3.

[0039] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the fluidity modifier described in step 1 is one or a mixture of polyethylene wax, polypropylene wax, paraffin, stearic acid, zinc stearate and calcium stearate. Others are the same as specific embodiments 1 to 4.

[0040] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the moisture content of the ethylene-methyl acrylate-glycidyl methacrylate copolymer, polylactic acid and wood fiber described in step 1 is all below 3%. Other aspects are the same as specific embodiments 1 to 5.

[0041] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: in step 2, a high-speed mixer is used to mix the weighed ethylene-methyl acrylate-glycidyl methacrylate copolymer and polylactic acid for 3min to 8min at a rotation speed of 1000rmp to 1500rmp, and then a single screw extruder is used to melt extrude at a temperature of 120°C to 230°C and a main engine speed of 10rmp to 20rmp, and finally cooled, crushed and granulated to a particle size of 2mm to 8mm to obtain a blended polymer. The rest is the same as specific embodiments 1 to 6.

[0042] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in step three, a high-speed mixer is used to mix the weighed wood fiber, fluidity modifier and the blended polymer prepared in step two for 3min to 8min at a rotation speed of 1000rmp to 1500rmp, and then a twin-screw extruder is used to perform secondary melt extrusion at a temperature of 140°C to 200°C and a main engine speed of 30rmp to 60rmp, and the mixture is cooled, crushed and granulated to a particle size of 2mm to 8mm, and finally dried to a moisture content of <2% to obtain wood-plastic granules. The rest is the same as specific embodiments one to seven.

[0043] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 4, the wood-plastic pellets are drawn using a single-screw wire drawing machine under the conditions of a temperature of 110°C to 170°C, a main engine speed of 15Hz to 25Hz, and a traction speed of 10rmp to 20rmp. The rest is the same as specific embodiments 1 to 8.

[0044] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: Step 2 uses a single screw extruder to perform a melt extrusion at two temperature zones of 130°C and 220°C, respectively, and a main engine speed of 10rmp to 20rmp; Step 3 uses a twin screw extruder to perform a secondary melt extrusion at seven temperature zones of 150°C, 160°C, 170°C, 180°C, 170°C, 160°C and 150°C, respectively, and a main engine speed of 30rmp to 60rmp; In step 4, a single screw wire drawing machine is used to draw the wood plastic pellets at two temperature zones of 165°C and 125°C, respectively, and a main engine speed of 15Hz to 25Hz and a traction speed of 10rmp to 20rmp. The rest is the same as specific embodiments 1 to 9.

[0045] The following examples are used to verify the beneficial effects of the present invention:

[0046] Embodiment 1:

[0047] A method for preparing a high-toughness wood-plastic composite wire for 3D printing is carried out according to the following steps:

[0048] 1. Weighing:

[0049] Weigh 10 parts by mass of ethylene-methyl acrylate-glycidyl methacrylate copolymer (EMA-GMA), 58 parts of polylactic acid (PLA), 30 parts of wood fiber and 2 parts of flowability modifier;

[0050] The mass percentage of glycidyl methacrylate monomer in the ethylene-methyl acrylate-glycidyl methacrylate copolymer is 8%.

[0051] The polylactic acid has a melt mass flow rate of 7 g / 10 min at a temperature of 210° C. and a load of 2.16 kg;

[0052] The wood fiber is wood powder; the mesh number of the wood fiber is 120-150 mesh;

[0053] The fluidity modifier is polyethylene wax;

[0054] The ethylene-methyl acrylate-glycidyl methacrylate copolymer and polylactic acid are dried at a temperature of 60° C. for 6 hours, and the moisture content is below 3%;

[0055] The wood fibers are dried at a temperature of 103°C until the moisture content is below 3%;

[0056] 2. One-step melt extrusion:

[0057] Using a high-speed mixer, at a rotation speed of 1500 rpm, the weighed ethylene-methyl acrylate-glycidyl methacrylate copolymer and polylactic acid are mixed for 5 minutes, and then melt-extruded once using a single-screw extruder at a temperature of 130° C. in a temperature zone 1, 220° C. in a temperature zone 2, and a main engine rotation speed of 15 rpm, and finally cooled, crushed, and granulated to a particle size of 2 mm to 8 mm to obtain a blended polymer;

[0058] 3. Secondary melt extrusion:

[0059] Using a high-speed mixer, at a speed of 1500 rpm, the weighed wood fiber, the fluidity modifier and the blended polymer prepared in step 2 are mixed for 5 minutes, and then a twin-screw extruder is used to perform secondary melt extrusion at temperatures of 150° C., 160° C., 170° C., 180° C., 170° C., 160° C. and 150° C. in temperature zones 1 to 7, respectively, and the main engine speed is 40 rpm, and the mixture is cooled, crushed and granulated to a particle size of 2 mm to 8 mm, and finally dried to a moisture content of <2% to obtain wood-plastic granules;

[0060] 4. Wire drawing:

[0061] Under the conditions of 165°C in temperature zone 1, 125°C in temperature zone 2, 20Hz main engine speed and 15rmp pulling speed, the wood-plastic granules are drawn by a single screw wire drawing machine, and then water-cooled and drawn and rolled to obtain a high-toughness wood-plastic composite wire; the diameter of the high-toughness wood-plastic composite wire is 1.75±5mm.

[0062] Example 2: This example is different from Example 1 in that: in step 1, 20 parts of ethylene-methyl acrylate-glycidyl methacrylate copolymer (EMA-GMA), 48 parts of polylactic acid (PLA), 30 parts of wood fiber and 2 parts of fluidity modifier are weighed by weight. The rest is the same as Example 1.

[0063] Example 3: This example is different from Example 1 in that: in step 1, 30 parts of ethylene-methyl acrylate-glycidyl methacrylate copolymer (EMA-GMA), 38 parts of polylactic acid (PLA), 30 parts of wood fiber and 2 parts of fluidity modifier are weighed by weight. The rest is the same as Example 1.

[0064] Comparative experiment: The difference between this comparative experiment and Example 1 is that: the use of ethylene-methyl acrylate-glycidyl methacrylate copolymer is eliminated; 68 parts of polylactic acid (PLA), 30 parts of wood fiber and 2 parts of fluidity modifier are weighed by weight in step 1; step 2 is eliminated. The rest is the same as Example 1.

[0065] The wood-plastic particles prepared in Examples 1 to 3 and step 3 of the comparative experiment were hot pressed to obtain mechanical test pieces, and bending tests were performed according to ASTMD 790-10, tensile properties tests were performed according to ASTMD 638-14, and impact strength tests were performed according to ASTMD 6110. The test results are shown in Table 1 below:

[0066] Table 1

[0067] category Embodiment 1 Embodiment 2 Embodiment 3 Comparative experiment Bending strength / MPa 21.06 18.84 16.28 46.98 Tensile strength / MPa 8.16 17.98 8.98 27.01 Elongation at break / % 4.56 2.31 2.62 4.50 <![CDATA[Impact strength / kJ·m -2 > 8.00 14.63 17.80 5.71

[0068] As can be seen from the table, the embodiment uses wood powder as a filler for thermoplastic wires, which not only gives the material a natural wood feel, but also reduces the material use cost. The use of ethylene-methyl acrylate-glycidyl methacrylate copolymer (EMA-GMA) as a toughening agent between wood fiber and polylactic acid effectively improves the impact strength of the composite material. Compared with the comparative experiment, the impact strength is increased by 211.7%, and the toughness is improved, which makes it possible to print wood fiber / polymer composite products with good performance or special functions.

[0069] Figure 1 This is a physical picture of the high-toughness wood-plastic composite wire prepared in Example 1; as can be seen from the figure, the high-toughness wood-plastic composite wire prepared in Example has stable dimensions and a smooth surface.

[0070] Embodiment 4:

[0071] The high-toughness wood-plastic composite wire prepared in Example 1 is used for 3D printing, and the specific method is as follows:

[0072] The Cure modeling was output as an stl. file, and the 3D model was sliced ​​by Bamboo Studio software to obtain a g.code file. Before printing, the high-toughness wood-plastic composite wire was dried in a blast drying oven at 60°C. After drying, it was printed using a fused deposition type 3D printer. The model used was Tuozhu X1, and the printing conditions were set as shown in Table 2. The sample was obtained after 3D printing using the high-toughness wood-plastic composite wire.

[0073] Table 2

[0074] Print platform temperature 35℃ Print nozzle temperature 210℃ Print layer height 0.12mm Print speed 50mm / s for the first floor; 200mm / s for the exterior wall; 300mm / s for the interior wall Sparse filling 15% Hot bed bonding Brim1 layer

[0075] Figure 2 This is a real picture of the sample after 3D printing using high-toughness wood-plastic composite wire in Example 4; as can be seen from the figure, the sample has a good shape, stable size, no warping, and smooth edges, and has good application prospects.

Claims

1. A method for preparing a high-toughness wood-plastic composite wire for 3D printing, characterized in that It is carried out in the following steps:

1. Weighing: Weigh 1 to 30 parts of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 35 to 65 parts of polylactic acid, 10 to 40 parts of wood fiber and 1 to 3 parts of fluidity modifier according to mass proportions; 2. One-step melt extrusion: The weighed ethylene-methyl acrylate-glycidyl methacrylate copolymer and polylactic acid are mixed evenly, and then melt-extruded once using a single-screw extruder, and finally cooled, crushed and granulated to obtain a blended polymer; 3. Secondary melt extrusion: The weighed wood fiber, the fluidity modifier and the blended polymer prepared in step 2 are mixed evenly, and then a twin-screw extruder is used for secondary melt extrusion, cooling, crushing and granulation, and finally drying to obtain wood-plastic granules; 4. Wire drawing: The wood-plastic pellets are drawn using a single-screw wire drawing machine, and then water-cooled and reeled to obtain high-toughness wood-plastic composite wires for 3D printing.

2. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that The mass percentage of glycidyl methacrylate monomer in the ethylene-methyl acrylate-glycidyl methacrylate copolymer described in step 1 is 1% to 8%.

3. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that The polylactic acid described in step 1 has a melt mass flow rate of 3 g / 10 min to 10 g / 10 min under the conditions of a temperature of 210° C. and a load of 2.16 kg.

4. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that The wood fiber described in step 1 is one of wood powder, rice husk powder, bamboo powder, straw powder, fruit shell powder and bagasse, or a mixture of several of them; the mesh number of the wood fiber described in step 1 is 60-200 meshes.

5. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that The fluidity modifier described in step 1 is one of polyethylene wax, polypropylene wax, paraffin, stearic acid, zinc stearate and calcium stearate, or a mixture of several of them.

6. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that The moisture content of the ethylene-methyl acrylate-glycidyl methacrylate copolymer, polylactic acid and wood fiber described in step 1 is all below 3%.

7. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that In step 2, a high-speed mixer is used to mix the weighed ethylene-methyl acrylate-glycidyl methacrylate copolymer and polylactic acid for 3min to 8min at a rotation speed of 1000rmp to 1500rmp, and then a single-screw extruder is used to melt-extrude the mixture once at a temperature of 120°C to 230°C and a main engine speed of 10rmp to 20rmp. Finally, the mixture is cooled, crushed and granulated to a particle size of 2mm to 8mm to obtain a blended polymer.

8. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that In step 3, a high-speed mixer is used to mix the weighed wood fiber, the fluidity modifier and the blended polymer prepared in step 2 for 3min to 8min at a rotation speed of 1000rmp to 1500rmp, and then a twin-screw extruder is used to perform secondary melt extrusion at a temperature of 140°C to 200°C and a main engine speed of 30rmp to 60rmp, and the mixture is cooled, crushed and granulated to a particle size of 2mm to 8mm, and finally dried to a moisture content of <2% to obtain wood-plastic granules.

9. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that In step 4, the wood-plastic pellets are drawn using a single-screw wire drawing machine at a temperature of 110° C. to 170° C., a main engine speed of 15 Hz to 25 Hz, and a traction speed of 10 rpm to 20 rpm.

10. The method for preparing a high-toughness wood-plastic composite wire for 3D printing according to claim 1, characterized in that Step 2: melt extrusion is performed once using a single screw extruder under the condition that the temperatures of the two temperature zones are 130° C. and 220° C. respectively, and the main engine speed is 10 rpm to 20 rpm; Step 3: melt extrusion is performed twice using a twin screw extruder under the condition that the temperatures of the seven temperature zones are 150° C., 160° C., 170° C., 180° C., 170° C., 160° C. and 150° C. respectively, and the main engine speed is 30 rpm to 60 rpm; In step 4: the wood-plastic pellets are drawn using a single screw wire drawing machine under the conditions that the temperatures of the two temperature zones are 165° C. and 125° C. respectively, the main engine speed is 15 Hz to 25 Hz, and the traction speed is 10 rpm to 20 rpm.

Citation Information

Patent Citations

  • Woody 3D printing line

    CN104672616A

  • Toughened polylactic acid capable of being used for rapid forming and preparation method thereof

    CN105694401A

  • Polylactic acid wood-plastic composite wire rod and preparation method and application thereof

    CN108003582A

  • Method for preparing thermoplastic polyurethane elastomer toughened wood powder / polylactic acid composite wire for 3D printing

    CN109021519A

  • Preparation method of bamboo fiber / basalt fiber / polypropylene environment-friendly composite wire

    CN113845718A